2013
DOI: 10.3109/13693786.2013.800240
|View full text |Cite
|
Sign up to set email alerts
|

Genotype analysis based on intergenic spacer 1 sequences ofTrichosporon asahiicollected in Taiwan

Abstract: Among 32 Trichosporon asahii isolates collected in four rounds of the Taiwan Surveillance of Antimicrobial Resistance of Yeasts (TSARY) studies, conducted in 1999, 2002, 2006, and 2010, five different intergenic spacer 1 (IGS1) genotypes were detected. Genotype 1 was the most common (43.8%), followed by genotypes 3 (28.1%), 7 (12.5%), 5 (9.4%), and 4 (6.3%). Interestingly, genotype 7 was more prevalent in Taiwan than in other areas (P = 0.01); while we did not find a significant association between IGS1 genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…Details from 19 studies having tested at least 10 Trichosporon clinical isolates for a given species with a microdilution method are presented in Tables 3 – 8 (Arikan and Hasçelik, 2002 ; Paphitou et al, 2002 ; Ramos et al, 2004 ; Metin et al, 2005 ; Rodriguez-Tudela et al, 2005 ; de Oliveira Silva et al, 2008 ; Chagas-Neto et al, 2009 ; Taj-Aldeen et al, 2009 ; Thompson et al, 2009 ; Lemes et al, 2010 ; Mekha et al, 2010 ; Guo et al, 2011 ; Sun et al, 2012 ; Tsai et al, 2012 ; Hazirolan et al, 2013 ; Yang et al, 2013 ; Arabatzis et al, 2014 ; Taverna et al, 2014 ; Montoya et al, 2015 ). Up to now, there is no recommendation from the two main consortia (EUCAST and CLSI) regarding the AST of Trichosporon .…”
Section: Resultsmentioning
confidence: 99%
“…Details from 19 studies having tested at least 10 Trichosporon clinical isolates for a given species with a microdilution method are presented in Tables 3 – 8 (Arikan and Hasçelik, 2002 ; Paphitou et al, 2002 ; Ramos et al, 2004 ; Metin et al, 2005 ; Rodriguez-Tudela et al, 2005 ; de Oliveira Silva et al, 2008 ; Chagas-Neto et al, 2009 ; Taj-Aldeen et al, 2009 ; Thompson et al, 2009 ; Lemes et al, 2010 ; Mekha et al, 2010 ; Guo et al, 2011 ; Sun et al, 2012 ; Tsai et al, 2012 ; Hazirolan et al, 2013 ; Yang et al, 2013 ; Arabatzis et al, 2014 ; Taverna et al, 2014 ; Montoya et al, 2015 ). Up to now, there is no recommendation from the two main consortia (EUCAST and CLSI) regarding the AST of Trichosporon .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our results found that genotype 3 strains exhibited higher AMB MICs (Ն2 g/ml) than did genotype 1 strains (P ϭ 0.009). Sun et al pointed out that genotype 3 strains were more capable of hemolysis and biofilm formation (12), and Yang et al found that genotype 4 isolates were more resistant to antifungal agents (28). However, more work is needed on the possible association between genotypes, virulence, and drug resistance in the pathogenesis of human invasive infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, from 2010 onward the first sporadic cases of Trichosporon spp . resistant to voriconazole were reported [ 9 , 10 ], and a recent study from Greece reported that 38 % of Trichosporon isolates had a MIC ≥ 2 mg/L for voriconazole [ 11 ]. Most of these strains were susceptible to at least one other triazole, and treatment failures were not described in this study.…”
Section: Discussionmentioning
confidence: 99%